Recent progress in the bio- and chronostratigraphic understanding of the upper Frasnian (Upper Devonian) sedimentary sequences in Armenia - Danelian, T.; Serobyan, V.; Hairapetian, V.; Tsatryan, M.; Khachatryan, S.; Yeghiazaryan, M.; Avagyan, N.; Hambardzumyan, T.; Kirakosyan, G.; Harutyunyan, L.; Lokteva, V.; Gasparyan, A.; et al. (ՀՀ ԳԱԱ «Գիտություն» հրատ)
Recently obtained biostratigraphic results in terrigenous sequences (shales and sandstones) intercalated between brachiopod-bearing limestones constitute an important breakthrough in our understanding of the chronostratigraphic framework of the Frasnian–Famennian transitional interval. More precisely, miospores obtained from the Ertych section constrain the entire terrigenous sequence to the late Frasnian, while acritarchs, prasinophytes and chitinozoans found in the same samples establish that their accumulation took place in marine environments. Conodonts extracted from the Noravank section establish that the lower part of the terrigenous interval, dominated by shales, was accumulated during the linguiformis conodont zone. Taking into account the combined chronostratigraphic evidence in the two sections, it may be inferred that the terrigenous sequence accumulated in less than 240 thousand years. Our results establish, for the first time, a relatively precise time framework to describe and reconstruct marine and terrestrial paleoecosystems that existed in the northern edge of the megacontinent Gondwana. Բրախիոպոդներ պարունակող կրաքարերի միջև ընկած տերիգեն նստվածքային հաջորդականությունների (թերթաքարեր և ավազաքարեր) վերաբերյալ վերջերս ստացված կենսաշերտագրական տվյալները կարևոր առաջընթաց են Ֆրան–Ֆամեն անցումային միջակայքի ժամանակաշերտագրական կառուցվածքի ըմբռնման գործում։ Մասնավորապես, Էրտիչի կտրվածքից ստացված միոսպորները թույլ են տալիս սահմանափակել ամբողջ տերիգեն հաջորդականության տարիքը ուշ Ֆրանով։ Միևնույն ժամանակ, այս նույն նմուշներում հայտնաբերված ակրիտարխները, պրազինոֆիտները և խիտինոզոաները հաստատում են դրանց նստվածքակուտակումը ծովային միջավայրում: Նորավանքի կտրվածքի կոնոդոնտները ցույց են տալիս, որ տերիգենային միջակայքի ստորին հատվածը, որը հիմնականում ներկայացված է թերթաքարերով, կուտակվել է linguiformis կոնոդոնտային զոնային համապատասխանող ժամանակում։ Հաշվի առնելով երկու կտրվածքներից ստացված ժամանակաշերտագրական տվյալների ամբողջությունը, կարելի է եզրակացնել, որ տերիգեն հաջորդականության ձևավորումը տեղի է ունեցել ոչ ավել, քան 240 հազար տարվա ընթացքում։ Ստացված արդյունքները հնարավորություն են տալիս առաջին անգամ սահմանել համեմատաբար ճշգրիտ ժամանակային շրջանակներ Գոնդվանա գերմայրցամաքի հյուսիսային եզրին գոյություն ունեցած ծովային և ցամաքային պալեոէկոհամակարգերի նկարագրության և վերակառուցման համար։
Keywords: Paleontology